Becoming More Resilient during COVID-19: Insights from a Process Evaluation of Digital Resilience Training - Ang, Wei How Darryl; Chew, Han Shi Jocelyn; Ong, Yew Hui Nicholas; Zheng, Zhongjia James; Shorey, Shefaly; Lau, Ying (International Journal of Environmental Research and Public Health, 2022)
Resilience training is gaining attention as a strategy to build students’ resistance to adversity and promote their mental well-being. However, owing to inconsistencies and variations in the content and delivery of resilience training, more work is needed to examine students’ experiences and preferences to address issues relating to intervention fidelity. This study adopted a qualitative approach in exploring students’ experience of synchronous and asynchronous versions of a digital resilience training program. Seventeen students were interviewed using a semi-structured virtual face-to-face interview via Zoom. The thematic analyses unveiled four themes: embarking on a journey toward resilience, discovering strategies to develop resilience, finding a balance to benefit from resilience skill enhancement, and instilling resilience in the everyday. Future resilience training should consider students’ workload and interactivity to enhance their engagement. As being resilient is associated with better mental well-being, the findings of this study may support the development of future wellness programs.